Characteristics of orf1 and orf2 in the anfHDGK genomic region encoding nitrogenase 3 of Azotobacter vinelandii. - Mylona, P V (1996)
In Azotobacter vinelandii, the anfHDGK operon encodes the subunits for the third nitrogenase complex. Two open reading frames (orf1 and orf2) located immediately downstream of anfK were shown to be required for diazotrophic growth under Mo- and V-deficient conditions. We have designated orf1 and orf2 anfO and anfR, respectively. Strains (CA115 and CA116) carrying in-frame deletions in anfO and anfR accumulate the subunits for nitrogenase 3 under Mo-deficient diazotrophic conditions. AnfO and AnfR are required for nitrogenase 3-dependent diazotrophic growth and 15N2 incorporation but not for acetylene reduction. AnfO contains a putative heme-binding domain that exhibits similarity to presumed heme-binding domains of P-450 cytochromes. Amino acid substitutions of Cys-158 show that this residue is required for fully functional AnfO as measured by diazotrophic growth under Mo- and V-deficient conditions. The nucleotide sequence of the region located immediately downstream of anfR has been determined. A putative rho-independent transcription termination site has been identified 250 bp from the 3' end of anfR. A third open reading frame (orf3), located downstream of anfR, does not appear to be required for diazotrophic growth under Mo- and V-deficient conditions.